Sexual behavior and experience of sexual coercion among secondary school students in three states in North Eastern Nigeria (2006)
Background: Interest in the reproductive health of adolescents continues to grow throughout the world. Few studies had explored the reproductive health knowledge, sexual behavior and experience of sexual coercion among secondary school students in North Eastern states of Nigeria. The objectives of this descriptive survey were to collect data to plan appropriate interventions that meet the reproductive health knowledge, service and skills needs of students in Bauchi, Borno and Gombe states. Methods: Face-to-face interviews were conducted for 624 consenting students who were randomly selected from eighteen secondary schools using an 83-item structured questionnaire. Data were collected on demographic profile, reproductive health knowledge, sexual behavior and experience of sexual coercion. Results: The mean age of the respondents was 16.5 years. There were slightly more males (52%) than females (48%). Students' knowledge about, reproductive health was generally low even though girls had better knowledge than boys. Thirteen percent of the entire students had sexual experience; significantly more males (19%) than females (6%) had done so (p < 0.001). Among boys the age at sexual debut ranged from 10-26 with a mean of 15.7 and median of 16. By contrast, the age at first sex among girls ranged from 10 to 18 years with a mean and median of 16.1 and 17 years respectively. Only 24% of those who were sexually active used a condom during their last sexual encounter. Overall 11% of the students reported that they had been tricked into having sex, 9% had experienced unwanted touch of breast and backside, and 5% reported rape. Conclusion: Students low reproductive health knowledge and involvement in risky sexual activities predispose them to undesirable reproductive health outcomes.